Health in Hard Times - Bambra, Clare (Policy Press, 2019)
Available Open Access under CC-BY-NC licence and edited by a leading expert, this is an important book for anyone seeking to understand one of today's most significant determinants of health. How has austerity impacted on health and wellbeing in the UK? Health in Hard Times explores its repercussions for social inequalities in health. The result of five years of research, the book draws on a case study of Stockton-on-Tees in the north-east of England, home to some of the starkest health divides. By placing individual and local experiences in the context of national budget cuts and welfare reforms, it provides a holistic perspective on countrywide inequalities.